Morphological, proximate, and bioactive compound characteristics of three local avocado (Persea americana) varieties from Solok District, West Sumatra, Indonesia - RIFNI NOVITASARI; TUTY ANGGRAINI; HASBULLAH HASBULLAH; DINI HERVANI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Novitasari R, Anggraini T, Hasbullah, Hervani D. 2025. Morphological, proximate, and bioactive compound characteristics of three local avocado (Persea americana) varieties from Solok District, West Sumatra, Indonesia. Biodiversitas 26: 5360-5370. This study compares the morphological characteristics, proximate composition, and bioactive compound content of three local avocado (Persea americana) varieties from Solok District, West Sumatra: Mega Merapi, Mega Paninggahan, and Mega Gagauan. The methods used include exploratory research for morphological observations with 30 samples per variety. In addition, chemical analysis was conducted using the Completely Randomized Design (CRD) method with three replications. The variables observed were proximate, total sugar, tannin, and phenol. Data processing was carried out using Analysis of Variance (ANOVA) and continued with the Least Significant Difference (LSD) test. The results showed that Mega Gagauan had the most significant fruit weight (480.66 g) and fruit flesh (382.69%), as well as the highest water content (72.95%) and fat (4.79%) in the fruit seeds. The fruit flesh of this variety contains the highest carbohydrate (10.64%), fat (6.61%), and ash content (1.03%), with a low water content (81.02%). In comparison, Mega Paninggahan has a fruit height (12.44 cm) and seed weight (64.98 g) that are superior to the other two varieties, with carbohydrate content (27.84%), protein (1.91%) and ash content (1.28%) in the fruit seeds and protein (2.10%) in the fruit flesh that are higher than the other two varieties. Mega Merapi stands out with the highest water content (85.65%), polyphenol (102.64 mgGAE/g), and total sugar (20.60%) in the fruit flesh, while the fruit seeds contain tannin (0.61%) and polyphenol (943.45 mgGAE/g). Differences in peel color, texture, and flesh color were also found between varieties. These findings confirm significant variation in morphology, proximate composition, and bioactive compounds, which can inform the selection of superior varieties for consumption and inspire creative product development from avocado flesh and seeds.